2020
DOI: 10.1021/acs.jpca.0c09862
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Aqueous-Phase Decomposition of α-Hydroxyalkyl-Hydroperoxides

Abstract: Ozonolysis of unsaturated organic species with water produces α-hydroxyalkylhydroperoxides (α-HHs), which are reactive intermediates that lead to the formation of H 2 O 2 and multifunctionalized species in atmospheric condensed phases. Here, we report temperaturedependent rate coefficients (k) for the aqueous-phase decomposition of α-terpineol α-HHs at 283−318 K and terpinen-4-ol α-HHs at 313−328 K. The temporal profiles of α-HH signals, detected as chloride adducts by negative-ion electrospray mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…The formed aldehyde species are hydrated into geminal diols or isomerize into functionalized lactols in acidic aqueous media, consistent with experimental results: 56,58 Next, we measured the rate constant for the decomposition of α-HHs derived from ozonolysis of α-terpineol or terpinene-4-ol in water at different temperatures. 58 Arrhenius plot analysis yielded activation energies (E a ) of 17.9 ± 0.7 (pH 6.1, Figure 7) and 17.1 ± 0.2 kcal mol −1 (pH 6.2) for the decomposition of αterpineol and terpinen-4-ol α-HHs, respectively. 58 The uncertainty was obtained from linear-regression fitting.…”
Section: Fates Of Roohs In Aqueous Phasessupporting
confidence: 82%
See 1 more Smart Citation
“…The formed aldehyde species are hydrated into geminal diols or isomerize into functionalized lactols in acidic aqueous media, consistent with experimental results: 56,58 Next, we measured the rate constant for the decomposition of α-HHs derived from ozonolysis of α-terpineol or terpinene-4-ol in water at different temperatures. 58 Arrhenius plot analysis yielded activation energies (E a ) of 17.9 ± 0.7 (pH 6.1, Figure 7) and 17.1 ± 0.2 kcal mol −1 (pH 6.2) for the decomposition of αterpineol and terpinen-4-ol α-HHs, respectively. 58 The uncertainty was obtained from linear-regression fitting.…”
Section: Fates Of Roohs In Aqueous Phasessupporting
confidence: 82%
“…We have also found that the decomposition of α-HHs occurs over the course of minutes to hours, with lifetimes (τ 1/e ) that are dramatically affected by the water content, 57,59 pH, 56 and temperature 58 of the reaction solution, as well as the structure of the α-HH. 57,59 For example, α-HHs derived from ozonolysis of α-pinene with water were found to decay with τ 1/e = 62 min in a 20:80 (vol:vol) water:acetonitrile solution, but with τ 1/e = 14 min in a 60:40 solution.…”
Section: Fates Of Roohs In Aqueous Phasesmentioning
confidence: 74%
“…The present calculations also confirmed that H 2 O 2 could be an important byproduct of the decomposition of α-AHs in the aqueous phase, consistent with the previous theoretical result for α-Tp α-HHs. 15 A previous iodometry analysis of a mixture of 1 mM α-Tp + 0.2 mM NaCl + 0.06 mM O 3 + 0.1 mM HCl revealed that approximately 70% of O 3 was converted into H 2 O 2 and other peroxides in water. 38 Another experimental study on the aqueous-phase decomposition of α-acyloxyalkyl-hydroperoxides derived from α-pinene CIs with carboxylic acids found that H 2 O 2 is a key decomposition product.…”
Section: Resultsmentioning
confidence: 98%
“…The present calculations also confirmed that H 2 O 2 could be an important byproduct of the decomposition of -AHs in the aqueous phase, consistent with the previous theoretical result for -Tp -HHs. 15 A previous iodometry analysis of a mixture of 1 mM -Tp + 0.…”
Section: Theoretical Calculations For the Decay Of -Ahs In The Aqueo...mentioning
confidence: 99%
See 1 more Smart Citation